The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.15407/microbiolj84.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Comamonas testosteroni under Hexachlorobenzene Loading Conditions

Abstract: Changes in the lipid composition in bacterial membranes are considered to be the most important adaptation mechanisms to adverse chemical factors. The aim of the study was to compare the hexachlorobenzene effects on the fatty acid composition of total lipids Comamonas testosteroni. Methods. The study was performed with C. testosteroni UCM B-400 and B-401, B-213 strains. Bacteria were grown in the Luria-Bertrani (LB) liquid medium containing 10 and 20 mg/L of hexachlorobenzene (HCB). After cultivation, the biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Th e lipid composition of bacterial membranes is an important component that plays a significant role in the adaptation of microorganisms to adverse living conditions (Dimova & Iutynska, 2022). Th e study of the fatty acid composition of the microbial preparation Sporazyn revealed the highest content of unsaturated fatty acids (67.47%), while the ratio of saturated to unsaturated was 0.48 (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…Th e lipid composition of bacterial membranes is an important component that plays a significant role in the adaptation of microorganisms to adverse living conditions (Dimova & Iutynska, 2022). Th e study of the fatty acid composition of the microbial preparation Sporazyn revealed the highest content of unsaturated fatty acids (67.47%), while the ratio of saturated to unsaturated was 0.48 (Fig.…”
Section: Methodsmentioning
confidence: 98%